A training model of an automated storage and retrieval system (AS/RS) with customized Warehouse Management System (WMS) - Tee, Kian Sek (2007)
AS/RS is a key industrial automation system that has drastically reduced the workforce needed to run a warehouse. Via a computer-controlled system, many intensive labour jobs are taken over by the system, including tediously moving and sorting heavy load from the minute of receving until shipping to customers, intensive paperwork to record goods receiving and order receipts. Somehow, in real business, the system is always complex in the perspective of engineering considerations, depending on the nature of the business, tending to upgrading and modification from time to time. It is desirable that the engineering training curve would provide an engineer perspective in industry design concepts and contemporary technologies to the students, not in the operator prospective. This project is intended to develop a training model of AS/RS for the engineering students. The learning curves are provided through three levels in the system integration. The device level illustrates basic input and output devices that are carefully choosen. The controller level processes all input information from the input devices and host computer. The supervisory level implements graphic user interface for system monitoring and control for the operator. The training model also emphasizes in three design concepts, flexibility, expandability and modularity. Flexibility will allow a broad spectrum of application environments and extend application life. Expandability will allow application in areas not yet defined. Modularity will enhance modification and maintenance.